Comparison of Gravimetric Method with UV-Vis Spectrophotometry for Determination of Reaction Order in Natural Dyes Adsorption Process - Wijayanti, Imas Eva; Erliasna, Emia; Solfarina, Solfarina (J-PEK (Jurnal Pembelajaran Kimia), 2023)
The order of the reaction is the number of concentration factors that affect the speed of a chemical reaction. The reaction order can be used to determine how the adsorption process is in the colouring process based on determining the linear regression equation of the R square value. This study aims to compare the gravimetric method with the UV-Vis spectrophotometric method in determining the reaction order in chlorophyll samples of the natural dye papaya leaves. This study used a quantitative method to determine the value of the reaction order of the papaya leaf natural dye, with data analysis techniques including gravimetric method analysis to determine chlorophyll content, UV-Vis spectrophotometry to determine the value of chlorophyll absorbance and linear regression to determine the order of the reaction. The results showed that the two methods followed first order with an R-value of 0.951 for the gravimetric method and 0.994 for the UV-Vis spectrophotometric method. REFERENCESAisy, G. A. R. (2018). Analysis of the Chlorophyll Content of Papaya Leaf Extract (Upload Papaya L.) Against Extraction Time Variations Using a Hodothermal Extractor. Diponegoro University, (1969), 4–27.Azizah, H. P., & Utami, B. (2016). Utilization of Green Dyes from Papaya Leaves (Carica papaya L.) As a Natural Textile Dyes. UNY National Chemistry Seminar, (October 2016).Fauziah, L., & Wakidah, M. (2019). Extraction of Papaya Leaves (Carica papaya L.) Using Ultrasonic Cleaner. EKSAKTA: Journal of Sciences and Data Analysis, 19(1), 35–45.Khofya, A., & Aji, M. P. (2018). Papaya Leaf Extract (Upload Papaya L.) as a natural dye in batik cloth. Indonesian Journal of Natural Science Education (IJNSE), 1(1), 13–17.Manurung, M. (2012). Mangosteen Peel Application (Garcinia Mangostana L.) As a Natural Dyes on Cotton Fabrics by Pre-Mordanting. Journal of Chemistry, 6(2): 183-190.Matitaputty, J. K., Ufie, A., Ima, W., & Pattipeilohy, P. (2022). Implementation of Education for Sustainable Development (ESD) Through Ecopedagogy in Learning at SMP Negeri 8 Ambon. BUDIMAS Journal, 04(1). http://journal.um-surabaya.ac.id/index.php/JKM/article/view/2203Namirah, I., Affifah, I., Wijayanti, I. E., & Langitasari, I. (2019). Study of Natural Coloring Plants in the Outer Baduy Community. EduChemia (Journal of Chemistry and Education), 4(2), 204.Pujilestari, T. (2015). Review: Sources and Utilization of Natural Dyes for Industrial Purposes Dynamics of Crafts and Batik, 32(2), 93–106. Retrieved from https://media.neliti.com/media/publications/61575-ID-review-sumber-dan-pemanfaatan-zat-warna.pdfRibeiro, M. G. T. C., Costa, D. A., & Machado, A. A. S. C. (2010). “Green Star”: A holistic green chemistry metric for evaluation of teaching laboratory experiments. Green Chemistry Letters and Reviews, 3(2), 149–159.Saputra, B. W. (2008). Adsorption System. 6–21. Tugas Akhir Sarjana. Jurusan Teknik Elektro Universitas Indonesia, Jakarta.Sugiyono. (2011). Quantitative Research Methods, Qualitative and R&D. Bandung: Alphabet.